2022
DOI: 10.1021/acsami.2c02685
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Harnessing High Rate and Cycle Performance from Graphite Electrodes in Potassium-Ion Batteries

Abstract: Potassium-ion batteries (PIBs) have been lauded as the next-generation energy storage systems on account of their high voltage capabilities and low costs and the high abundance of potassium resources. However, the practical utility of PIBs has been heavily encumbered by severe K metal dendrite formation, safety issues, and insufficient electrochemical performance during operationsindeed critical issues that underpin the need for functional electrolytes with high thermal stability, robust solid− electrolyte in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…131,132 XPS has been found to be a valuable tool in studying both SIBs and KIBs. [133][134][135][136][137][138] Going even further into novel systems, we nd multivalent-ion batteries based on magnesium and calcium that present further unique challenges and require some unique solutions. 139,140 Fig.…”
Section: Interfacial Reactions In 'Beyond Li-ion' Technologiesmentioning
confidence: 99%
“…131,132 XPS has been found to be a valuable tool in studying both SIBs and KIBs. [133][134][135][136][137][138] Going even further into novel systems, we nd multivalent-ion batteries based on magnesium and calcium that present further unique challenges and require some unique solutions. 139,140 Fig.…”
Section: Interfacial Reactions In 'Beyond Li-ion' Technologiesmentioning
confidence: 99%
“…For example, Chagas et al 148 149 reviewed IL electrolytes for sodium-ion batteries from ion conductivity thermal and cycling stability aspects and pointed out that cations including pyrrolidinium-based, quaternary ammonium, quaternary phosphonium are currently the most stable cations in IL electrolyte candidates for sodium-ion batteries. Furthermore, for potassium-ion batteries, in addition to the application of [Pyr][FSI] or [Pyr][Tf 2 N] ([Pyr] + = pyrrolidinium) summarized by Zhou et al, 35 Kaushik et al 150 applied a high-concentrated K[FSI]-Cs[FSI] electrolyte and achieved a higher rate and cycle performance from graphite electrodes than that with pyrrolidinium-based electrolytes at 70 °C. This improvement is attributed to the SEI-free design, which reduces internal resistance.…”
Section: Ils As Electrolytes For Batteriesmentioning
confidence: 99%
“…In essence, the occurrence of Na metal deposition dominates over Na + ion intercalation into graphite. Recently, Kaushik et al reported that an inorganic IL K[FSA]À Cs[FSA] (x(K[FSA]) = 0.54) was successfully applied as the electrolyte in potassium-ion batteries in combination with graphite negative electrodes at 343 K. [44] The absence of organic cations facilitated stability at elevated temperatures; however, the melting point of this IL was as high as 336 K. [12b]…”
Section: P E R S O N a L A C C O U N T T H E C H E M I C A L R E C O R Dmentioning
confidence: 99%